12С(15N, 14С) 13N reaction mechanisms at energy 81 MeV and 14С + 13N nuclei interaction - А. Т. Rudchik; А. А. Rudchik; О. E. Kutsyk; К. Rusek; K. W. Kemper; E. Piasecki; A. Stolarz; A. Trczinska; Val. М. Pirnak; О. А. Ponkratenko; I. Strojek; E. І. Koshchiy; et al. (Ядерна фізика та енергетика)
The 12С(15N, 14С)13N reaction at the energy Еlab(15N) = 81 MeV for ground and excited states of 14С and 13N nuclei was investigated. New experimental data of the reaction cross-sections were obtained. The data were analyzed within the coupled reaction channels method (CRC). The 15N + 12С elastic scattering as well as the more important reactions of nucleon and cluster transfers were included in the channels-coupling scheme. In the CRC-calculations, the Woods - Saxon potentials (WS) were used for the interactions of 15N + 12С and 14С + 13N nuclei in the entrance and exit reaction channels. WS potential parameters for the reaction entrance channel were deduced previously from CRC-analysis of the 15N + 12С elastic and inelastic scattering data, then the WS potential parameters for the reaction exit channel were deduced from the fitting of 12С(15N, 14С)13N reaction data. The spectroscopic amplitudes of nucleons and clusters, used in the CRC-calculations, were computed within translational invariant shell model. As the results of the reaction CRC-analysis, the information about WS potential of 14С + 13N nuclei interaction as well as about mechanisms of nucleons and clusters transfer was deduced. It was found, that transfers of protons and 2n-clusters dominate in this reaction. It was also studied the differences of the reaction CRC cross-sections calculated using the 14С + 13N і 14С + 14N potentials in the reaction exit channel (isotopic effects).